2019
DOI: 10.1017/s0021859619000509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term nutrient management practices on soil micronutrient concentrations and uptake under a rice–wheat cropping system

Abstract: A field experiment was conducted to study the long-term effects of nutrient management practices on micronutrient concentrations in soil and their uptake by crops under a long-term rice–wheat cropping system. The treatments comprised different combinations of N, P, K, Zn and farm yard manure (FYM), used as nutrient management practices. After 25 years of continuous cropping, the higher grain yields and uptake of iron (Fe), manganese (Mn), copper (Cu) and zinc (Zn) were obtained when FYM was applied along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…There were no significant interaction in potassium uptake in grain and straw between tillage practices and fertilization levels during both year of experimentation and pooled. Similar findings were also reported by Singh et al [26], Yadav et al [27] and Puniya et al [28].…”
Section: Potassium Uptake In Grain and Straw (Kg Ha -1 )supporting
confidence: 90%
“…There were no significant interaction in potassium uptake in grain and straw between tillage practices and fertilization levels during both year of experimentation and pooled. Similar findings were also reported by Singh et al [26], Yadav et al [27] and Puniya et al [28].…”
Section: Potassium Uptake In Grain and Straw (Kg Ha -1 )supporting
confidence: 90%
“…Soil nutrient imbalances is one of the main obstacles of continuous cropping ( Puniya et al., 2019 ). In the present study, PC treatment reduced all soil nutrient content and enzyme activities compared to the other three cropping systems, with its value close to that of PR.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, application of NPSZnB blended >100 kg ha −1 (in Vertisol) and >125 kg ha −1 (in Cambisol) showed better agronomic value on wheat than the NP alone in Ayiba condition. Similarly, Puniya et al (2019) reported that higher uptake of Fe, Mn, Cu, and Zn were obtained with combined FYM and NPK application compared to mineral sources of NPK alone. Now, emphasis is also placed on improving the use efficiency of fertilizers through the 4R nutrient stewardship principle ( i.e ., right source, right rate, right time, and right placement) ( IPNI, 2014 ).…”
Section: Resultsmentioning
confidence: 84%